Bisnis dalam Perspektif Islam (Al-Quran) - Joko Prasetiyo (STES Islamic Village, 2022)
Trade or business is an honorable working in Islamic teachings, because there are so many verses of the Qur'an and hadith of the Prophet that mention and explain the norms of trade. The Prophet ‘s appreciation for a trade is very high. Therefore, this study aims to elaborate the concept of business in the perspective of Islam (Al-Qur'an) and to find out the principles of business, financial management and ethics of business. Thematic interpretation is a method that uses a contemporary theme approach, which requires problem solving from reviewing verses, munasabah verses, asbabun nuzul, interpretation of verses and hadiths related to business and current problems and looking for the best solution for the problems. Among the many verses of the Qur’an that talk about trade, this study only uses one verse as the main verse (source). While the other verses are supporting verses. The main verse is surah an-Nisaa '(4:29). The choice of this verse because the verse (an-Nisaa' (4:29), speaks about the prohibition of utilizing the wealth on a false manner and the necessity of trading based on willingness. While the other verses are the supporting verses. Among the supporting verses is surah al-Baqarah (2: 282) which mentions the concept of recording (accounting) in trading activities and ethics in business, this is revealed by Allah SWT in His word in Surah An-Nuur (24: 37). The findings of this study are: the concept of trade that the Qur'an talks about are the principles that guide the trade throughout time, in accordance with the eternal character of the Qur'an. Thus, the Qur'an does not explain the concept of trade in detail. If the Qur'an talks in detail, it will be difficult to answer the various trade problems that are always changing and developing in the face of the challenges of the times.